Sosialisasi Kesadaran Finansial dan Mental Siswa Kelas XII Hadapi Dunia Kerja dan Kuliah - Milatina Laksmita Dewi; Dina Ulayya Azizah; Zefi Nafira Arifiani (LPPM Universitas Panca Bhakti, 2026)
This Community Service activity aims to enhance financial awareness, mental health, and psychological aspects of twelfth-grade students in facing the transition to the workforce and higher education. The implementation of the activity is carried out through three stages, namely preparation, implementation, and evaluation. The preparation stage includes coordination with the school and the development of materials; the implementation stage is conducted through interactive material delivery, discussions, and question-and-answer sessions; while the evaluation stage is carried out to measure the effectiveness of the activity through observation of participant engagement, feedback, and comparison of students’ understanding before and after the activity. The target of this activity is twelfth-grade students of SMA NU 03 Mualimin Weleri, who serve as the main participants. The results of the activity indicate an improvement in students’ understanding and awareness of the importance of personal financial management, such as financial planning and expense control, as well as increased awareness of the importance of mental health in dealing with the pressures of the workforce and higher education. In addition, the interactive approach used has proven to enhance participant engagement throughout the activity. Therefore, this activity provides a positive contribution in preparing students to face future challenges more effectively, both from financial and psychological perspectives. The evaluation of this activity also serves as a basis for the development of future PkM programs to be more effective and sustainable.